2011
DOI: 10.1177/0278364911402406
|View full text |Cite
|
Sign up to set email alerts
|

Undulatory swimming in sand: experimental and simulation studies of a robotic sandfish

Abstract: A previous study of a sand-swimming lizard, the sandfish, revealed that it swims within granular media at speeds up to 0.4 body-lengths/cycle using body undulations (approximately a single period sinusoidal traveling wave) without limb use. Inspired by the organism, we develop a numerical model of a robot swimming in a simulated granular medium to guide the design of a physical device. Both in simulation and experiment the robot swims limblessly subsurface at speeds up to 0.3 body-lengths/cycle and, like the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
72
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(72 citation statements)
references
References 60 publications
(70 reference statements)
0
72
0
Order By: Relevance
“…A previous study of sandfish showed that η is independent of particle size over an order of magnitude (Maladen et al, 2011b). Also, simulation of sandfish has shown that graingrain friction has a small effect on sandfish η while body-grain friction has a larger effect (Maladen et al, 2011a). Increasing particle-particle friction by 50% caused a 14% increase in η while increasing particle-body friction by 50% caused an 84% decrease in η.…”
Section: Influence Of Particle Propertiesmentioning
confidence: 93%
See 1 more Smart Citation
“…A previous study of sandfish showed that η is independent of particle size over an order of magnitude (Maladen et al, 2011b). Also, simulation of sandfish has shown that graingrain friction has a small effect on sandfish η while body-grain friction has a larger effect (Maladen et al, 2011a). Increasing particle-particle friction by 50% caused a 14% increase in η while increasing particle-body friction by 50% caused an 84% decrease in η.…”
Section: Influence Of Particle Propertiesmentioning
confidence: 93%
“…Korta and colleagues found that mechanosensory input may act to regulate this temporal frequency and allow gait adaptation in response to different surroundings (Korta et al, 2007). Studies of our sandfish models (Maladen et al, 2011a;Maladen et al, 2011b;Maladen et al, 2011c) could be used to determine the extent of muscle power reduction as a result of decreasing frequency with depth for a sandswimmer.…”
Section: Depth Dependencementioning
confidence: 99%
“…No tapering in height of the body along its length is considered, as doing so results in the model rising as it moves forward owing to drag-induced granular lift. This lift results from the vertical component of the normal force on an inclined surface dragged through a granular medium and is discussed in Ding et al [50] and Maladen et al [51]. We perform simulations for a square tube body shape, and to more closely match the animal we perform simulations using a model tapered in the coronal plane (figure 3a) with width varying linearly from the snout tip to 1/6 bl, and from 3/5 bl to the tail tip.…”
Section: Numerical Sandfish Simulationmentioning
confidence: 95%
“…For the smooth robot, the animal in 0.3 mm (loosely and closely packed media) [22] and 3 mm particles ( §2), and in model predictions ( § §3 and 4) in simulated 3 mm glass particles, the values of h are all close to 0.5. This suggests that subsurface locomotion in granular media is largely independent of media properties like particle size and density [51].…”
mentioning
confidence: 99%
“…Locomotion in confined environments offers several challenges for animals (18) that include limitations due to body shape changes (19,20), restricted limb mobility (21), increased body drag, and reduced thrust development (22). Examining the motion repertoire of soft-bodied animals (23), such as annelids (19), insect larvae (24), and molluscs (25), has offered insight into a range of strategies used to move in confined spaces.…”
mentioning
confidence: 99%